Från den gruvliga till den ljuvliga sidan : - odling i industristaden Falun - Axelsson Karlqvist, Jimmy; Berger, Åsa (META – Historiskarkeologisk tidskrift, 2025)
Falun has been the subject of numerous archaeological excavations over the years. Thereby we have gained more knowledge of the living conditions in Falun ca 1600-1700. The history of the town Falun cannot be written without mentioning the copper mine, which is in a sense Sweden's oldest environmental contamination. Even though the mine is closed, its former industry still affects the environment. Our understanding of the historical environment of Falun is therefore in a state of alteration. In recent years, new perspectives and methods have resulted in unearthed traces of urban cultivation. The town is separated by the stream Faluån. The west side of the stream is usually referred as “the mine side”, where the common perception is that not many plants grew due to the toxic smoke and contaminated soil. The east side is usually referred to the “nice” or “delightful side” with lush green vegetation.